Digestible energy content of corn- vs sorghum-based dried distillers grains with solubles and their effects on growth performance and carcass characteristics in finishing pigs - Feoli, C.; Monge, C.; Gugle, Terry L.; Carter, S.D.; Cole, N.A.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to determine the nutritional value of corn- and sorghum-based dried distillers grains with solubles (DDGS). In Exp. 1, 120 finishing pigs (average initial weight of 244 lb) were used in a 19-d DE determination. The reference diet was 97% corn with vitamins, minerals, and amino acids added to meet or exceed all NRC suggested nutrient concentrations. Treatments were corn-based (Sioux River Ethanol, Hudson, SD and MGP Ingredients, Atchison, KS) and sorghum-based (US Energy Partners, Russell, KS and Western Plains Energy, Oakley, KS) DDGS substituted as 50% of the reference diet in place of corn. Comparisons among the treatments indicated that DDGS from corn had 101 kcal/lb greater DE than DDGS from sorghum (P<0.02). However, DE was different among the sources of corn-based DDGS (P<0.001) and sorghum-based DDGS (P<0.03) suggesting that plant of origin affects DE of DDGS. In Exp. 2, 176 finishing pigs (average initial weight of 141 lb) were used in a 72-d growth assay. There were 11 pigs/pen and four pens/treatment with feed and water consumed on an ad libitum basis until the pigs were slaughtered at an average weight of 286 lb. Treatments were a corn-soybean meal-based control diet and diets with 40% corn-based, high-energy DDGS (Sioux River Etha-nol), 40% corn-based, moderate-energy DDGS (MGP Ingredients), and 40% sorghum-based, moderate-energy DDGS (US Energy Partners). Pigs fed the control diet had greater overall ADG (P<0.003) and digestibility of DM (P<0.001), N (P<0.02), and GE (P<0.001) compared to pigs fed the DDGS treatments. Among the DDGS treatments, pigs fed the high-energy product had lower overall ADG (P<0.06), ADFI (P<0.02), and digestibility of DM (P<0.03) but tended to have better F/G (P<0.07) than pigs fed the moderate energy DDGS sources. As for carcass data, hot carcass weight (P<0.001) and dressing percentage (P<0.003) were greater and iodine value of jowl fat lower (P<0.001) for pigs fed the control vs DDGS treatments. Among the DDGS treatments, pigs fed the sorghum-based DDGS had greater dressing percentage (P<0.04) and lower iodine value (P<0.001) than pigs fed the corn-based DDGS. Backfat thickness (P>0.58) and percentage carcass lean (P>0.25) were not affected by treatment. In conclusion, plant of origin and substrate used in the fermentation process (corn vs sorghum) affected the nutritional value of DDGS for finishing pigs.
Keywords: Swine; DDGS; Feed ingredient; Meat quality; Sorghum